2013
DOI: 10.3892/ijo.2013.1894
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the expression of CLU isoforms in endometrial proliferative diseases

Abstract: Clusterin (CLU) is a nearly ubiquitous multifunctional protein synthesized in different functionally divergent isoforms, sCLU and nCLU, playing a crucial role by keeping a balance between cell proliferation and death. Studying in vivo CLU expression we found a higher mRNA expression both in neoplastic and hyperplastic tissues in comparison to normal endometria; in particular, by RT-qPCR we demonstrated an increase of the specific sCLU isoform in the neoplastic and hyperplastic endometrial diseases. On the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 54 publications
(101 reference statements)
3
13
0
Order By: Relevance
“…Specifically, the neoplastic transformation may manifest itself with the alteration of synthesis of the two CLU transcript variants with a dominance of CLU2 over CLU1, resulting in the promotion of transformed cell survival. This hypothesis is in agreement with previous studies suggesting that the survival of cancer cells is related to over-expression of CLU2 and down-regulation of CLU1 transcripts [ 21 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Specifically, the neoplastic transformation may manifest itself with the alteration of synthesis of the two CLU transcript variants with a dominance of CLU2 over CLU1, resulting in the promotion of transformed cell survival. This hypothesis is in agreement with previous studies suggesting that the survival of cancer cells is related to over-expression of CLU2 and down-regulation of CLU1 transcripts [ 21 ].…”
Section: Discussionsupporting
confidence: 94%
“…These inspections revealed multiple possible CLU transcript variants, two of which identified by the Signature ID [ 29 ] c7175b345e:9 and 1057fea355:9, overlapping to the sequences of the NCBI database with accession number NM_001831, CLU1 and NR_038335, CLU2. These two variants all contain nine exons, and each of them presents a unique exon 1 and shares the remaining 2–9 exons [ 21 ]. Although the CLU1 transcript variant was not present in other cancer tissues [ 11 , 30 ] the reason why it is taken into consideration is because it stood out by having substantially more sequence support than the others in the ASPicDB in silico analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Clusterin appears to be subjected to post-transcriptional regulation. 12 An analysis (at writing) of the NEI bank libraries of eye tissues (http://neibank.nei.nih.gov/index.shtml) showed that the iris was the tissue where clusterin was the most abundantly expressed gene. Clusterin ranked first in the iris, 15 th on the lens, 27 th in cornea, and 29 th in the retina.…”
Section: Exfoliation Syndrome and Exfoliation Material What Is It Wmentioning
confidence: 99%
“…14 This finding would be consistent with the presence of a post-transcriptional regulation for this gene, which has been described in the endometria. 12 …”
Section: Exfoliation Syndrome and Exfoliation Material What Is It Wmentioning
confidence: 99%